(untitled) (Publicaciones en Ciencias y Tecnología, 2008)
A model of the simulation and functional evaluation for a Community Manager System (CMS), on a Multiagent Web Operating System (MWOS) is presented. Following a reference design and concepts associated with swarm intelligence, the evaluation focused on auto-organization and emergent community management requirements using a gathering algorithm based on the behavioral emergent patterns of ant colonies. Both, Intra and Inter-wise CMS resources were searched using a dynamic auto-organizative management approach according to CMS requirements and the SWOM’s objectives.